Psychometric properties of the transgender identity stigma scale in Argentina - Ramos-Santiago, Jeffrey Wilmer; Caballero, Romina; Zalazar, Virginia; Radusky, Pablo D.; Cardozo, Nadir; Brunori, Boris; Ramos-Pibernus, Alixida; Cupertino, Ana Paula; Mejía, Raúl; Cartujano-Barrera, Francisco; Aristeguí, Inés (Frontiers in Psychology, 2025)
IntroductionTransgender identity stigma (TIS) threatens the well-being of transgender and gender-diverse (TGD) individuals. To the best of our knowledge, there are no validated TIS measures developed for TGD individuals living in Argentina. The purpose of this study was to evaluate the psychometric properties of a TIS scale among a sample of TGD individuals living in Argentina.MethodsThis study consisted of a secondary data analysis of the TransCITAR cohort study. Participants were 484 TGD individuals living in Buenos Aires, Argentina. Items from the HIV Stigma Index and the Everyday Discrimination Scale were combined and adapted to design the TIS scale. Item reduction analyses were carried out. Keyser-Meyer-Olkin (KMO) test of sampling adequacy and Bartlett’s Test of Sphericity were examined to verify the factorability of the scale. Exploratory factor analyses (EFA) were conducted using a principal component method with promax rotation to identify the underlying factors of the scale.ResultsThe KMO value was 0.83 and the Bartlett’s Test of Sphericity showed correlations between the variables (χ2 = 5,901.26, d.f. = 66, p < 0.001). Upon demonstrating factorability, an EFA was calculated with the 12 items selected for the final version of the TIS scale. Two factors were extracted, explaining 72% of the total variance.ConclusionThe TIS scale showed great internal consistency, reliability, and construct and criterion validity among TGD individuals living in Argentina, with applicability in both research and clinical settings.